OPTIMALISATION OF THE SI ENGINE TIMING ADVANCE FUELED BY LPG - Paweł FABIŚ; Marek FLEKIEWICZ (Scientific Journal of Silesian University of Technology. Series Transport)
This study is an attempt to determine the control parameters of the control system for gaseous fuels currently used for driving vehicles. It presents the selected dynamic parameters of the car obtained when fueling the engine with petroleum-based LPG. This paper attempts to determine the optimal timing advance of the gas-air mixture and the efficiency of its processing in the drive system of the tested vehicle driven by a four-cylinder engine with a 1.6 dm. More so, this article includes an analysis of the influence of the optimised power charts of the engine on the dynamics of the motion of a motor vehicle running on gaseous fuel. To present changes in the dynamics of movement, indicators and parameters determining changes in the dynamics of vehicle movement, such as dynamic coefficient, acceleration and flexibility were used. Through this analysis, it is possible to verify the optimised power and torque waveform and determine whether the vehicle dynamics improved.